Third year EFL learner’s perceptions towards self- reliance during the corona virus era - MEDDAS RAOUIA . BENHERIRA GHANIMA, Dr. TOUATI MOURAD (university of M'sila, 2023)
Abstract : With the corona virus disease 2019, a major change to remote education arrangements has arisen, as it is clear; the pandemic had side effects, particularly in the scope of education and English as a foreign language (EFL) teaching and learning, students at all levels were encouraged to continue learning despite the difficulties they faced during the crisis, relying primarily on themselves.,Accordingly, The present investigation examines third year EFL learners perceptions towards self-reliance at Mohammed Boudiaf University of M’sila, as well as the challenges they encountered along their learning process during the pandemic era , and the three years health protocol. In order to achieve the aims of this descriptive study, A mixed method was used to obtain a significant answers to the research questions, semi –structured a questionnaire was designed for forty EFL students at the department of English. It revealed that regardless the Corona virus' detrimental effects on students' academic performance; it helped them become more self-reliant in the light of the challenges they encountered, and overcome their inability to comprehend lessons in the absence of teacher's interaction . By the end, we suggest some recommendations that are essential to equip our learners to be self-reliant, and improvise them for any expected circumstances.
Keywords: Keywords: perceptions, self –reliance, pandemic era (covid 19), EFL learners